2005
DOI: 10.1007/s10665-005-2732-6
|View full text |Cite
|
Sign up to set email alerts
|

Convective and Absolute Instability in the Incompressible Boundary Layer on a Rotating Disk in the Presence of a Uniform Magnetic Field

Abstract: The stability of a conducting fluid flow over a rotating disk with a uniform magnetic field applied normal to the disk, is investigated. It is assumed that the magnetic field is unaffected by the motion of the fluid. The mean flow and linear stability equations are solved for a range of magnetic field-strength parameters and the absolute/convective nature of the stability is investigated. It is found that increasing the magnetic field parameter is in general stabilizing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 17 publications
3
29
0
Order By: Relevance
“…Such an instability, which was also observed experimentally by [19], manifests itself as a wave pattern of spiral vortices inclined at an higher angle of about 20 • to the radius vector, but with a much reduced wavenumber than that corresponding to the inviscid instability of [12]. The influence of a magnetic field on the convective/absolute instability mechanism was recently studied in [21].…”
Section: Introductionmentioning
confidence: 67%
“…Such an instability, which was also observed experimentally by [19], manifests itself as a wave pattern of spiral vortices inclined at an higher angle of about 20 • to the radius vector, but with a much reduced wavenumber than that corresponding to the inviscid instability of [12]. The influence of a magnetic field on the convective/absolute instability mechanism was recently studied in [21].…”
Section: Introductionmentioning
confidence: 67%
“…The disturbance components of the above system are determined later by solving the form of the Navier-Stokes equations that results from substituting these quantities in (1)(2)(3)(4)(5)(6), and subtracting out the mean flow equations, satisfying (8)(9). Having linearized the equations for small perturbations, we find that the linearized Navier-Stokes operator has coefficients independent of θ , and hence, the disturbances can be decomposed into a normal mode form proportional to e iR(βθ−ωt) .…”
Section: Linear Stability Equationsmentioning
confidence: 99%
“…This mechanism is well-documented in the literature for a non-conducting Von Kármán flow; see for instance [3][4][5] amongst many others. Moreover, the recent work of Jasmine and Gajjar [6] concluded that the presence of a normal magnetic field acts in the way of stabilizing the absolute instability mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations